Very close I⋯As and I⋯Sb interactions in trimethylpnictogen-pentafluoroiodobenzene cocrystals. Issue 1 (1st December 2021) - Bujak, Maciej; Stammler, Hans-Georg; Vishnevskiy, Yury V.; Mitzel, Norbert W.
Abstract : The unusually short, for any experimentally characterized molecular (co)crystal, directional C–I⋯As and C–I⋯Sb halogen bonds have been engineered in the supramolecular reactions of the in situ cocrystallized (CH3 )3 E (E = As or Sb) with C6 F5 I. Abstract : The cocrystals (CH3 )3 As·C6 F5 I (1 ) and (CH3 )3 Sb·C6 F5 I (2 ) were generated in situ from equimolar mixtures of their components. 1 and 2 show very close I⋯As and I⋯Sb directional intermolecular interactions. They are 0.5 and 0.7 Å shorter than the sums of van der Waals radii, respectively, and are the shortest C–I⋯As and C–I⋯Sb halogen bonds of this type found for experimentally characterized molecular (co)crystals. Comparisons of the packing motifs and contacts in 1 and 2 with those in (CH3 )3 As (3 ), (CH3 )3 Sb (4 ) and C6 F5 I (5 ) illustrate the occurrence and hierarchy of the specific interactions. The heteromolecular components in 1 and 2 are assembled by I⋯As, I⋯Sb and F⋯H interactions. There are no significant intermolecular As⋯As contacts in 3, but Sb⋯Sb interactions in 4 . Molecules in 5 are mainly associated by I⋯F, F⋯F and F⋯C contacts. The intermolecular interactions observed in the (co)crystals correspond to the calculated electrostatic potentials.